Novel Dry Hyaluronic Acid–Vancomycin Complex Powder for Inhalation, Useful in Pulmonary Infections Associated with Cystic Fibrosis - Magi, María S. (2024)
Impact Factor: 4.9 (2023). 5-Year Impact Factor: 5.5 (2023). Se publicó como preprint en: https://www.preprints.org/manuscript/202402.0587/v1